2014
DOI: 10.1155/2014/460942
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Polyanion onto Large Alpha Alumina Beads with Variably Charged Surface

Abstract: Adsorption of strong polyelectrolyte, poly(styrenesulfonate), PSS, of different molecular weights onto large α-Al2O3 beads was systematically investigated as functions of pH and NaCl concentrations. The ultraviolet (UV) absorption spectra of PSS at different pH and salt concentrations confirmed that the structure of PSS is independent of pH. With the change of molecular weight from 70 kg/mol (PSS 70) to 1000 kg/mol (PSS 1000), adsorption amount of PSS increases and proton coadsorption on the surface of α-Al2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Thus, adsorption of inorganic pollutants onto surfactant modified laterite could not be fitted by Langmuir and Freundlich models. Fortunately, a twostep model presented by Zhu and Gu [32] with a general adsorption isotherm equation was successfully applied to various types of surfactants, polymers, and dyes adsorption isotherms for numerous systems [32][33][34][35][36][37]. Adsorptive removal of both organic and inorganic pollutants by using surfactant modified alumina was thoroughly studied by Pal and coworkers [2,16,[38][39][40][41], indicating that surfactant modified solid adsorbent is a novel adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, adsorption of inorganic pollutants onto surfactant modified laterite could not be fitted by Langmuir and Freundlich models. Fortunately, a twostep model presented by Zhu and Gu [32] with a general adsorption isotherm equation was successfully applied to various types of surfactants, polymers, and dyes adsorption isotherms for numerous systems [32][33][34][35][36][37]. Adsorptive removal of both organic and inorganic pollutants by using surfactant modified alumina was thoroughly studied by Pal and coworkers [2,16,[38][39][40][41], indicating that surfactant modified solid adsorbent is a novel adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…The proton co-adsorption upon the adsorption of organic ions is important to predict the mechanism and adsorbed structures. In our previously published papers, the concomitant proton adsorption is significant in the cas e of surfactant adsorption [20] while the proton co-ads orption upon polyelectrolye adsorption can be also determined [29]. Nevertheless, the adsorption amount of proton during adsorption of NC on α-A l2O3 is not significant after ad justing pH to original value.…”
Section: Structure Of Adsorbed Nc Onto α-Al2o3mentioning
confidence: 90%
“…Based on the two-step model, a general adsorption isotherm equation can be derived. This equation was successfully applied to numerous types of surfactant and polymer adsorption isotherms for various systems [26][27][28][29]. The mult ilayer model which was introduced by the Brunauer-Emmett-Te ller (BET) [30], was used to describe adsorption isotherms of the ionic dyes [21,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…4. clearly shows that higher ionic strength imparts high positive surface charge density which leads to increase in adsorption due to higher electrostatic attraction [50].…”
Section: Effect Of Surfactant: Co-surfactant Ratio On Nanoparticles Smentioning
confidence: 99%
“…Study revealed that fluoride adsorption on studied adsorbent might not follow the D-R adsorption isotherm model. Two step adsorption model [50,53,54] was applied to describe the adsorption isotherms and by using this model, maximum adsorption capacity was found to be 140.54 mg/g (Fig.5 a). Equilibrium constant for first layer adsorption (k 1 , L/mg) and multilayer adsorption (k 2 , (L/mg) n-1 ) were found to be 0.0141 L/mg and 0.4473 (L/mg) n-1 respectively.…”
Section: Fluoride Ions Adsorption Using Nanoparticlesmentioning
confidence: 99%